Tailoring acid-base properties on metal-free zeolite from Indonesia kaolin to enhance the CO2 hydrogenation to CH4 - Sholeha, Novia Amalia; Dewanto, Bintang; Jovita, Stella; Nugraha, Reva Edra; Taufiq-Yap, Yun Hin; Ulfa, Maria; Fauzi, Anees Ameera; Abdul Jalil, Aishah; Bahruji, Hasliza; Prasetyoko, Didik (Elsevier, 2024)
The catalytic thermal conversion of carbon dioxide is essential for carbon capture, storage, and utilization, helping to reduce CO2 emissions and potentially stimulating future economic activities. Zeolite Y, ZSM-5, BEA, and A were synthesized using the hydrothermal technique from Indonesian kaolin to examine the potential use of zeolite as a catalyst without metal nanoparticles. In the absence of metal, catalytic activity for CO2 methanation relies solely on textural properties and basicity-acidity. Zeolite Y exhibits the highest CO2 conversion at 36.64 % and attained 100 % of CH4 selectivity at 400 °C. The exceptional CO2 conversion of zeolite Y relies on a high basicity level of 1.02 mmol/g, as shown by CO2-TPD analysis, and a relatively low acid site concentration of 1.48 mmol/g, as determined by NH3-TPD analysis. ZSM-5, BEA, and zeolite A, demonstrated CO2 conversion of 29.85 %, 23.86 %, and 12.15 %, respectively. Stability studies revealed ZSM-5 maintains methane (CH4) selectivity of 94 %, which is only slightly lowered by 6 % for 30 hours, while zeolite Y achieved 90 % selectivity for 26 hours. The presence of mesopores in zeolite ZSM-5 reduced coke or carbon production, maintaining crystalline framework.